A cross sectional study of chronic suppurative otitis media and its associated factors among primary school children in rural and urban areas of Aligarh, India - Parvez, Ashib; Khan, Zulfia; Hashmi, SF; Khan, Mohammad Shibly (International Journal Of Community Medicine And Public Health, 2017)
Background: Chronic suppurative otitis media in the school children is an important public health concern as it may lead to hearing loss and thereby affecting the intellectual performance. Present study aims to estimate the prevalence of CSOM and to determine some of its socio-demographic, environmental, personal hygiene and nutritional status factors among the primary school children, in the rural and urban field practice areas of Dept. of Community Medicine, JNMCH, AMU, Aligarh, India. Methods: An estimated sample of 630 was chosen. The number of children from the individual schools was taken as per probability proportionate to size (PPS) while Stratified random sampling was used to identify the individual subject. The children were interviewed using semi-structured format followed by general and otoscopic examination. Results: The overall prevalence of Chronic Suppurative Otitis Media (CSOM) among study population was estimated to be 6.1% (95% CI 4.4-8.2) which was found to be 7% (95% CI 5.0-9.6) in rural areas and 1.8% (95% CI 0.5-6.3)in urban areas. It was found to significantly associated (p<0.05) with nutritional status of the child and standard of living Index (SLI), while no significant association (p>0.05) was observed with other socio-demographic variables such as father’s occupation, mother’s education, over-crowding and exposure to smoke. Conclusion: present study shows a high prevalence of CSOM especially in the rural areas, which warrants the urgent action to be taken for preventing the future occurrence of hearing impairment. Conclusions: The prevalence of CSOM in our study was found to be high as per the WHO otitis media expert committee recommendations. CSOM is an important preventable cause of hearing impairment, so this level of prevalence represents a cause of concern.